A Nucleolin-Targeted Multimodal Nanoparticle Imaging Probe for Tracking Cancer Cells Using an Aptamer - Hwang, Do Won; Ko, Hae Young; Lee, Jung Hwan; Kang, Hyungu; Ryu, Sung Ho; Song, In Chan; Lee, Dong Soo; Kim, Soonhag (Journal of Nuclear Medicine, 2010)
The recent advances in molecular imaging techniques, using cancer-targeting nanoparticle probes, provide noninvasive tracking information on cancer cells in living subjects. Here, we report a multimodal cancer-targeted imaging system capable of concurrent fluorescence imaging, radionuclide imaging, and MRI in vivo. A cobalt-ferrite nanoparticle surrounded by fluorescent rhodamine (designated MF) within a silica shell matrix was synthesized with the AS1411 aptamer (MF-AS1411) that targets nucleolin (a cellular membrane protein highly expressed in cancer) using N-(3-dimethylaminopropyl)-N-ethylcarbodiimide (EDC). This purified MF-AS1411 particle was bound with 2-(p-isothio-cyanatobenzyl)-1,4,7-triazacyclonane-1,4,7-triacetic acid (p-SCN-bn-NOTA) chelating agent and further labeled with (67)Ga-citrate (MFR-AS1411). The shape and size distribution of MFR-AS1411 were characterized by transmission electron microscope (TEM). The cellular distribution of the nucleolin protein using the MFR-AS1411 nanoparticle was detected by fluorescence confocal microscopy. Phantom MR images were obtained as the concentration of MFR-AS1411 increased, using a 1.5-T MRI scanner. In vivo (67)Ga radionuclide imaging and MRI were performed using a gamma-camera and a 1.5-T MR imager, respectively. TEM imaging revealed MF and MFR-AS1411 to be spheric and well dispersed. The purified MFR-AS1411 nanoparticle showed specific fluorescence signals in nucleolin-expressing C6 cells, compared with MFR-AS1411 mutant (MFR-AS1411mt)-treated C6 cells. The rhodamine fluorescence intensity and (67)Ga activity of MFR-AS1411 were enhanced in a dose-dependent manner as the concentration of MFR-AS1411 was increased. The (67)Ga radionuclide was detected in both thighs of the mice injected with MFR-AS1411, whereas the MFR-AS1411 mutant (MFR-AS1411mt) administration revealed rapid clearance via the bloodstream, demonstrating that MFR-AS1411 specifically targeted cancer cells. Bioluminescence images in the C6 cells, stably expressing the luciferase gene, illustrated the in vivo distribution. T2-weighted MR images of the same mice injected with MFR-AS1411 showed dark T2 signals inside the tumor region, compared with the MRI signal of the tumor region injected with MFR-AS1411mt particles. We developed a nanoparticle-based cancer-specific imaging probe using the AS1411 aptamer in vivo and in vitro. This multimodal targeting imaging strategy, using a cancer-specific AS1411 aptamer, can be used as a versatile imaging tool for specific cancer diagnosis.